Peculiarities of Heart Rhythm Variability in Children and Adolescents with Arrhythmias in the Presence of Comorbidity of the Upper Gastrointestinal Tract - Potapenko, S. V. (Zaporozhye Medical Journal, 2016)
Objective. To study peculiarities of the heart rhythm variability in children with heart rhythm disorders depending on the concomitant pathology of the upper part of the gastrointestinal tract. Material and methods of the research. 91 children from 15 to 17 years were under the supervision. The Ist group consisted of children with heart rhythm disorders on a background of chronic pathology of the upper gastrointestinal tract. The IInd group consisted of children with the pathology of the upper part of the gastrointestinal tract without heart rhythm disorders. The III group consisted of children with heart rhythm disorders without gastrointestinal pathology. The next methods were used: anamnesis analysis, physical examination, fiberoptic esophagogastroduodenoscopy and Holter monitoring of the heart functioning. Results: by comparison of the children from the I and the II groups, it was founded that children with upper gastrointestinal pathology (the II group) are prone to the predominance of the sympathetic VNS component on the background of parasympathetic activity reduction. (SDNNi 79,08±22,4 ms versus 101,53±37,91 ms, and rMSSD 56,93±20,97 ms versus 84,04±60,76 ms, р<0,05). Predomination of sympathetic activity in children from the IInd group was confirmed by low pNN50 rate (25,38±11,88 % versus 34,52±18,54 %, р<0,05). Children from the Ist group towards the children from the IIIrd group were characterized by lover HRV rates (SDNNi 70,54±28,21 ms versus 101,53±37,91 ms, and rMSSD 50,26±32,13 ms versus 84,04±60,76 ms, р<0,05), which also denotes sympathetic regulation strengthening and inactivation of the parasympathetic VNS component in children with the heart rhythm disorders on the ground of the upper gastrointestinal pathology. Conclusions. In children with heart rhythm disorders, in case of upper gastrointestinal pathology, lower rates of the VHR time analysis are more common. This fact demonstrates strengthening of the sympathetic regulation and inactivation of the VNS. Determined peculiarities of vegetative homeostasis are reasonably unfavorable factors in the context of the development of complications or even more complicated disease progress. In such way, children with heart rhythm disorders can be recommended vegetative homeostasis testing and, in case of activity predomination of sympathetic VNS component on the ground of parasympathetic activity decrease, it is necessary to study pathology of the upper part of the gastrointestinal tract as one of the reasons of the heart rhythm disorders.